Ανα-προσανατολίζοντας το Θεατή: Το «Άλλο» Θέατρο και η Αναθεώρηση των Θεατρικών Κωδίκων - Σακελλαρίδου Έλση (Σύγκριση/Comparaison/Comparison, 2017)
In recent years social groups marginalized in terms of class, race, ethnicity, gender and sexual preference have tried, through their dynamic theatre practice, to subvert the hegemony of the white, middleclass, heterosexual male in the production and reception of spectacle. Feminist film and theatre theorists and practitioners in particular have already explored the mechanisms of the male gaze in the construction and interpretation of images (in parallel to the male construction of narrative and discourse) and experimented with new strategies which aim at destroying this exclusive inscription of male desire on the screen and the stage. Furthermore they are working towards forestalling instead a polyvocal subjective inscription in the filmic and theatrical text which would invite a similar multiplicity in audience reception.